2020
DOI: 10.3390/ma13163455
|View full text |Cite
|
Sign up to set email alerts
|

PEG Grafted Polymethacrylates Bearing Antioxidants as a New Class of Polymer Conjugates for Application in Cosmetology

Abstract: The amphiphilic copolymers of poly(ethylene glycol) methyl ether methacrylate (MPEGMA) and alkyne functionalized 2-hydroxyethyl methacrylate (AlHEMA) were synthesized by controlled atom transfer radical polymerization (ATRP). The reactions were carried out using the standard ATRP initiator ethyl α-bromoisobutyrate, (EiBBr) and the “bio”initiator bromoester derivative of 4-n-butylresorcinol (4nBREBr2). Two substances with antioxidant activity used in cosmetology, (±)-α-lipoic acid (LA) and ferulic acid (FA), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…The comparison of signal intensities in the 1 H NMR spectra provides further evidence for the formation of ester bonds between cellulose –OH groups and DDMAT carboxyl (–COOH) groups. The results showed after polymerization by PEGMA, the poly­(PEGMA) peaks at (a) 1.2 ppm, (b) 1.8 ppm, (c) 3.4–3.5 ppm, and (d) 3.3 ppm. , This confirmed that all steps of synthesis were done successfully. Also, the ratio of PEGMA to cellulose was determined by using the integral calculation under the peak of about 1.2 ppm for poly­(PEGMA) and about 4 ppm for cellulose.…”
Section: Resultssupporting
confidence: 57%
“…The comparison of signal intensities in the 1 H NMR spectra provides further evidence for the formation of ester bonds between cellulose –OH groups and DDMAT carboxyl (–COOH) groups. The results showed after polymerization by PEGMA, the poly­(PEGMA) peaks at (a) 1.2 ppm, (b) 1.8 ppm, (c) 3.4–3.5 ppm, and (d) 3.3 ppm. , This confirmed that all steps of synthesis were done successfully. Also, the ratio of PEGMA to cellulose was determined by using the integral calculation under the peak of about 1.2 ppm for poly­(PEGMA) and about 4 ppm for cellulose.…”
Section: Resultssupporting
confidence: 57%
“…The differences in release profiles suggested the advantage of the "tailor-made" polymer carriers that could release the active substance under the appropriate conditions, which would depend on the specific use of the cosmetic or medical product. Comparing these micellar carriers with previously described conjugates also based on AlHEMA/MPEGMA copolymers, the latter ones bound less to the active substance, i.e., ferulic or lipoic acid (13-38%) [47]. Moreover, it took longer, up to 4 h, to release the usually lower amount of the conjugated bioactive molecules (~50%) than in the case of micelles.…”
Section: Resultsmentioning
confidence: 66%
“…The resulting copolymers of alkyne-functionalized 2-hydroxyethyl methacrylate (AlHEMA) and methyl methacrylate (MMA) or poly(ethylene glycol) methyl ether methacrylate (MPEGMA), i.e., P(AlHEMA-co-MPEGMA) and P(AlHEMA-co-MMA), were subjected to a "click" reaction with azide functionalized polymers, i.e., biodegradable poly(ε-caprolactone) (PCL), hydrophilic poly(ethylene glycol) (PEG) or azide functionalized low-molecular weight active substances, such as FA and LA. PEG graft copolymers P((HEMA-graft-PEG)-co-MMA) [23] and P((HEMA-graft-PCL)-co-MPEGMA) [24] for micellar systems loaded with the active substance, i.e., ARB, and the conjugates varied with the "click" active substance such as P((HEMA-click-FA)-co-MPEGMA) and P((HEMA-click-LA)-co-MPEGMA) [25] were synthesized ( Figure 1). The active substances are classified as antioxidants and protect against UV radiation, reduce wrinkles and skin discoloration.…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneously immortalized human epidermal keratinocytes (HaCaT) were purchased from CSL Cell Line Service GmbH (Eppelheim, Germany). Copolymers were synthesized and self-assembled to encapsulate active substance in aqueous solutions [23,24] or conjugated with FA and LA [25] according to previously described procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation